Saudi Arabia's Efforts to Maintain Global Oil Supply in the Persian Gulf (Global Focus, 2023)
The purpose of this study is to describe Saudi Arabia's efforts to maintain global oil supplies in the Persian Gulf. The research method used is descriptive qualitative using library research as a data collection technique. The results obtained from this study are that the efforts made by Saudi Arabia in maintaining global oil supplies in the Persian Gulf consist of two efforts, namely military and non-military efforts. Saudi Arabia's military efforts are joining the United States maritime coalition to carry out sentinel operations and conducting Sentinel Coalition Task Force (CTF) exercises as an increase in security cooperation between Saudi Arabia and the United States to protect oil shipments in the Persian Gulf. As for the non-military efforts made by Saudi Arabia, namely by holding an emergency meeting with the Gulf countries to inform them that a serious effort or effort is needed to protect the security of shipping in the Persian Gulf because of attacks that have occurred before, namely on two Saudi Arabian tankers which were sabotaged and released. the coast of Fujairah and drone attacks on oil fields or oil processing facilities in the Saudi cities of Khurais and Abqaiq.